Suatu Kegentingan Memaksa Menjadikan Peraturan Pemerintah Pengganti Undang-Undang Menjadi Undang-Undang - Iskandar Iskandar (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The State of Indonesia is a legal state that tries to keep things in order and make things clear for the people who work for the government. People and the government should always use the law as a guide when they do things in the name of the country or state. The Constitution gives the President, who is in charge of the government, the power to make a rule called a